Association between Hashimoto’s Thyroiditis and Thyroid Cancer in 64,628 Patients - Resende de Paiva, Christina; Grønhøj, Christian; Feldt-Rasmussen, Ulla; von Buchwald, Christian (Frontiers in Oncology, 2017)
Background: The incidence of thyroid cancer is increasing although explanatory causes are lacking. A link between cancer and inflammation is well documented but unclear for autoimmune thyroid diseases and thyroid cancer. We aimed to systematically review the association between Hashimoto’s thyroiditis and papillary, follicular, medullary, anaplastic thyroid carcinoma and thyroid lymphoma. Methods: PubMed, OVID Medline, Google Scholar and the Cochrane Library were searched from 1955 to 2016. The inclusion criteria were: age >18 years, ≥20 cases of Hashimoto’s thyroiditis (HT) or thyroid cancer (TC). We collectively examined the incidence of HT in TC and of TC in HT. Results: We identified 36 studies (64,628 subjects) published between 1955 and 2016 from 13 countries. We found a relative risk (RR) of HT among papillary thyroid cancer (PTC) of 2.36 (95% CI 1.55─3.29, p<0.001), a RR of PTC among HT of 1.40 (95% CI 1.07─1.85, p=0.016) and a RR of thyroid lymphoma (TL) among HT of 9.74 (95% CI 3.93─24.13, p<0.001). Conclusions: We report an association between HT and PTC and between HT and TL. No association was found between HT and follicular, medullary, or anaplastic thyroid cancer.